An exploration of the referral patterns of a community palliative care team to specialist palliative care outpatient physiotherapy for community based individuals with advanced cancer - CAHILL, FIONA (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2019)
Introduction: Physiotherapy is a core discipline within specialist palliative care (SPC) services and has been shown to contribute to the management of common symptoms associated with advanced cancer such as fatigue, breathlessness and decreased mobility. However, referral rates to physiotherapy for community based individuals range from 24 – 32%. Methods: This is a mixed methods study. A retrospective chart audit was completed using a specifically designed data extraction tool. It examined the profile of those with advanced cancer referred to SPC outpatient physiotherapy and comparing them to those not. Thirty-eight charts of those who referred to SPC physiotherapy and 102 chart of those who were not were selected and analysed using descriptive and comparative statistics. To gain a further insight into referral patterns, focus group interviews were held with members of the community palliative care (CPC) team to explore their understanding of the role of physiotherapy in SPC and what factors they consider prior to making a referral to physiotherapy. The transcripts of these interviews were analysed using a thematic content framework. Results: The overall referral rate to SPC physiotherapy was 27.4%. There was a significant difference in the age profile of those who were referred to SPC physiotherapy when compared to those who were not, with young individuals being referred to SPC physiotherapy (p=0.009). There was also a significant difference in the palliative performance scale between groups, with those who had a higher performance status being referred to SPC physiotherapy (p=0.035). Individuals referred to SPC physiotherapy were under the care of SPC services for a significantly longer period of time (p=0.023). Individuals with prostate cancer was the only cancer diagnosis in which there was a significant difference between groups (p=0.03). There was no difference in the symptoms or the severity of symptoms experience by individuals in both groups. The main reasons for referral to physiotherapy were decreased mobility (53%) and breathlessness (24%). The main themes identified from the focus group interviews were referral to physiotherapy, the expertise of physiotherapy practice within SPC services and development of SPC physiotherapy services. The participants discussed reasons that the refer to SPC physiotherapy including in response to symptoms and as a stepping stone into other services. They also discussed concerns that may influence their decision not to refer them to SPC physiotherapy. The participants reported that SPC physiotherapists had the skills and expertise to support those referred. They also discussed areas they would like the physiotherapy service to develop including providing a service in the individual’s homes. Discussion: Integrating the results from both phases of the research provides context regarding referral patterns to SPC physiotherapy. The main symptoms that participants identified in the focus groups as a reason to refer to SPC physiotherapy were decreased mobility and breathlessness which was supported from the medical chart audit. Participants in the focus group identified that they did not consider a referral to SPC physiotherapy in response to symptoms such as fatigue or pain. This was also evident within the medical chart audit. This highlights knowledge gaps regarding the role of SPC physiotherapy in the management of other symptoms. The participants also discussed factors which they consider prior to referring individuals for physiotherapy. This includes the individuals ability to participant in physiotherapy and the potential for meaningful outcomes. This may reflect the difference in the performance status and the age of those who were referred to physiotherapy. Implication for practice: This research supports the need for the development of a clear referral pathway to SPC physiotherapy in response to symptoms and consequences of illness. It also highlights the areas in which SPC physiotherapists need to provide education to those who are referring to SPC physiotherapy, including their role in the management of symptoms other than decreased mobility and breathlessness.
APPROVED
Keywords: Physiotherapy; Referral Patterns; Advanced Cancer; Specialist Palliative Care